Model Manajemen Peningkatan Publikasi Karya Tulis Dosen Sekolah Tinggi Agama Islam Kopertais Wilayah VI - Sriwardona, Sriwardona; Kurnia, Afdil (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Sekolah Tinggi Agama Islam (STAI) Kopertais Region VI lecturers tend to publish their written work in local journals, while their writing in the form of books with ISBNs, national journals and international reputations is still minimal. Overcoming this requires management. The aim of this research is to manage lecturers so that they produce written works in the form of books with ISBNs, national journals and international reputations. Research findings show that 1) publication of lecturers' written work tends to be in local journals, while writing in the form of ISBN books, national journals and international journals is still minimal, 2) the lecturer management model consists of seven steps including 1)Forecasting, 2) Objective, 3) Policies, 4) Programmes, 5) Schedules, 6) Procedures, 7) Budget.